Perubahan Pola Permukiman Orang Laut Suku Duano - Ichwan Azhari; Onggal Sihite; Ida Liana Tanjung (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2018)
This paper examines changes in Orang Laut settlements in two villages namely Tanjung Solok Village and Jambi Province Fisheries Village. Changes occurred from settlements on boats in the sea to settlements inside houses in the village. The research method used is an ethnographic research method whose characteristics are "researching informants - as subjects of research-in their daily environment". The researcher and the object under study interact intensely through in-depth observation of the object in accordance with the research objectives. In the two villages studied, the facts of the changes that have taken place over the past 30 years have been found, due to the incessant government programs to "settle" the Sea People to the mainland. Changes in the lives of the Orang Laut in the new and permanent villages have caused the loss of traditional knowledge of the Orang Laut in the maritime field. They changed from the Sea People who lived in a sea that was modest and full of wisdom to the sea and coastal ecosystems to become Sea People who lived on land with complex life, carried by the current of modernization and exploiting and destroying marine and coastal ecosystems.